Postevropsko mesto v Evropi - Venturi, Marco (Urbani izziv, 2002)
Established tools for forecasting urban development are evidently insufficient. Even most hypotheses seen as axiomatic in urbanisation processesare confronted by new phenomena on a daily basis. In the European tradition there is however a method, which allows definition of common methodsand answers: the analysis of ties in urbanisation processes. By analysis of quantitative observation, re-evaluation of the essence of public investments, identification of signs of urbanity and transformation of hierarchies the author offers a possibility for urban futures of European cities, which stems from relationships of contradicting pairs.
Keywords: Europe; Evropa; mesta; urbani razvoj; urbanism; urbanistično planiranje; urbanizacija; urbanizem